Personal and behavioural factors that influence physical activity in women living with metastatic breast cancer: a qualitative interview study - Mark Liu; Sharon Kilbreath; Jasmine Yee; Jane Beith; Justin McNab; Elizabeth Dylke (BMC Cancer)
Abstract Background Women living with metastatic breast cancer can benefit from physical activity. Presently, there is an absence of research outside of quantitative investigations on the benefits of structured programs. To enable effective physical activity advice and services, it is important to understand factors that may facilitate or prevent engagement. We therefore explored with women with metastatic breast cancer: (i) personal and behavioural factors that influenced physical activity, and (ii) the role of healthcare services in influencing engagement in being physically active. Methods Recruitment took place at a metropolitan cancer centre from November 2019 to January 2020. Women living with metastatic breast cancer were asked to participate in semi-structured interviews about physical activity, covering health-specific factors, goals, barriers, enablers, and interests. Interviews were recorded, transcribed and thematically analysed. Results Twenty-three women completed the interview, with a median age of 60 years (IQR: 20) and median time since metastatic diagnosis of 3.3 years (IQR: 3.0). Physical activity ranged from regular participation in structured exercise to simple incidental activity. Seven themes organised into three categories were identified. The category ‘personal context’ incorporated themes on: (1) both cancer and non-cancer related health factors; (2) time, work and family factors; and (3) exercise history and preferences. The category ‘strategies for physical activity’ incorporated themes on: (4) self-efficacy, and (5) routine and incidental activity. The category ‘role of health and physical activity services’ incorporated themes on: (6) tailored education and services, and (7) specific metastatic cancer services and considerations. Conclusions Participants expressed diverse experiences with physical activity, with common notions on how physical activity is beneficial but difficult in which to adhere. Whilst some barriers to engagement in physical activity were unique to having cancer, many were not specific to metastatic breast cancer. For example, some participants emphasised specific considerations resulting from their disease, while others primarily reported on general factors such as being time-poor or having conflicting priorities. A patient-centred approach tailored to this group’s health and behavioural context may be effective for women who are currently inactive to engage in physical activity.